Al-doped H2TiO3 ion sieve with enhanced Li+ adsorption performance. Issue 55 (28th October 2021) - Dai, Xianyang; Zhan, Honglong; Qian, Zhiqiang; Li, Jun; Liu, Zhong; Wu, Zhijian
Abstract : H2 TiO3 (HTO) is considered to be one of the most promising adsorbents for lithium recovery from aqueous lithium resources duo to its highest theoretical adsorption capacity. Abstract : H2 TiO3 (HTO) is considered to be one of the most promising adsorbents for lithium recovery from aqueous lithium resources duo to its highest theoretical adsorption capacity. However, its actual adsorption capacity is much lower owing to its unknown structure and incomplete leaching of lithium. After Al is doped into H2 TiO3 (HTO-Al), the adsorption capacity of HTO-Al is 32.12 mg g −1 and the dissolution of Ti is 2.53%. HTO-Al has good adsorption selectivity, and all the separation factors α are ≫1. Furthermore, HTO-Al also exhibits good cyclic stability and solubility resistance. After 5 cycles, the adsorption capacity remains 29.3 mg g −1 and the dissolution rate is 1.7%. Therefore, HTO-Al has potential application value for recovering Li + from aqueous lithium resources.